KATA-KATA TABU DALAM FILM FRIENDS WITH BENEFITS KARYA KEITH MERRYMAN & DAVID NEWMANN - LAWALATA, NADYA SARAH (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ASBTRACT This research is about â€œTaboo Words in Friends with Benefits Movie by Keith Merryman and David Newmannâ€. The objectives of this research are to identify and classify the types of taboo words and to analyze the causes of using them. This research is using a descriptive method. There are three steps to finish this research, first step is preparation, the writer watches the movie to find out the data. Second step is data collection, the writer collects the taboo words found in the movie and compares it with the movie script then the writer identifies and classifies the kinds of taboo words according to Wardhaughâ€™s (1986: 230) theory. Third step is data analysis, to analyze the data about the causes of using taboo words, the writer uses the theory from Jay (2009: 155). The results of this research: First, it shows that there are 139 taboo words found in this movie and they were classified into six types, those are sex, bodily function, certain game of animal, death, excretion, and religion. All of the types of taboo words according to Wardhaugh (1986: 230) are found in this movie. Second, it shows that the causes of using taboo words are to express the emotions, such as anger, happy, and surprised, to talk about sex, to joke and to insult. All of the causes of using taboo words according to Jay (2009: 155) are found in this movie. Â Keywords : Taboo Words; Movie: Friends with Benefits; Wardhaugh, Jay